2014
DOI: 10.1007/s00280-014-2441-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 5-formyltetrahydrofolate on the anti-tumor activity of pralatrexate, as compared to methotrexate, in HeLa cells in vitro

Abstract: Purpose To investigate the impact of 5-formytetrahydrofolate on the activities of pralatrexate, as compared to methotrexate (MTX), in vitro. Methods Cells were exposed to (6S)5-formyltetrahydrofolate (5-formylTHF) for 24h, before or after a 6h exposure to antifolates following which the cellular accumulation and activities of the drugs were evaluated in HeLa cells. Results A 24h delay between a 6h exposure to antifolates and a subsequent 24h exposure to 4 μM 5-formylTHF sustained the full activities of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The efficacy of PLX was shown to be related to the expression of RFC and DHFR ( Kinahan et al, 2020 ). This is in line with the findings that PLX is an excellent substrate for the RFC ( Figure 1 ; Wang et al, 2003 ; Visentin et al, 2014 ), but a poor substrate for PCFT and had a very low affinity for the folate receptors ( Table 1 ). In addition, it was shown that PLX was one log more potent than methotrexate in suppressing cell proliferation ( Tonner et al, 2006 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The efficacy of PLX was shown to be related to the expression of RFC and DHFR ( Kinahan et al, 2020 ). This is in line with the findings that PLX is an excellent substrate for the RFC ( Figure 1 ; Wang et al, 2003 ; Visentin et al, 2014 ), but a poor substrate for PCFT and had a very low affinity for the folate receptors ( Table 1 ). In addition, it was shown that PLX was one log more potent than methotrexate in suppressing cell proliferation ( Tonner et al, 2006 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although PLX has been tested in solid tumors ( Azzoli et al, 2007 ), it was ineffective. Compared with conventional antifolates, such as the classical methotrexate, PLX may be more tumor specific due to greater affinity for RFC ( Wang et al, 2003 ) and polyglutamylation efficiency by folylpolyglutamate synthetase ( O’Connor et al, 2011 ; Visentin et al, 2014 ). These two properties improve (tumor specific) cellular uptake and inhibit potential efflux following uptake.…”
Section: Introductionmentioning
confidence: 99%
“…To determine how standard of care drugs would perform in a spheroids MARY-X screen, several FDA-approved drugs known to be effective in solid tumor types as well as blood-borne malignancies, were evaluated. Spheroids were added to a multi-well plate (~30–50 spheroids/well) and then treated with vehicle only (DMSO) and increasing therapeutically-relevant drug doses as follows: bortezomib, lapatinib and doxorubicin (0–2.5 μM) [ 28 32 ], cisplatin (0–10 μM) [ 32 ] and methotrexate (0–20 μM) [ 33 ]. Therapeutically-relevant is defined as a drug dose that is either recorded in literature [ 32 , 34 37 ] or previous experiments as being the effective in vitro dose as determined in 2D cancer models.…”
Section: Resultsmentioning
confidence: 99%
“…41 In vitro studies suggested that a 24-hr delay between PDX exposure and subsequent exposure to leucovorin did not interfere with PDX cytotoxicity. 42 However, a 72-hr interval was required between a single exposure to leucovorin and subsequent exposure to PDX to sustain activity without requiring an increase in PDX concentration. Future studies that incorporate delayed administration of leucovorin may improve the side effect profile of this regimen.…”
Section: Discussionmentioning
confidence: 99%